Cognitive–behavioural group therapy versus guided self‐help for compulsive buying disorder: A preliminary study. (8th August 2011) - Müller, A.; Arikian, A.; de Zwaan, M.; Mitchell, J.E.
Abstract : Compulsive buying (CB) is defined as extreme preoccupation with buying/shopping and frequent buying that causes substantial negative psychological, social, occupational and financial consequences. There exists preliminary evidence that group cognitive–behavioural therapy (CBT) is effective in the treatment of CB. The present pilot study made a first attempt to compare group CBT for CB with telephone‐guided self‐help (GSH). Fifty‐six patients were allocated randomly to one of the three conditions: (1) group CBT ( n = 22); (2) GSH ( n = 20); and (3) a waiting list condition ( n = 14). The results indicate that face‐to‐face group CBT is superior not only to the waiting list condition but also to GSH. Patients who received GSH tended to have more success in overcoming CB compared with the waiting list controls. Given the sample size, the results must be considered as preliminary and further research is needed to address the topic whether GSH also could be a helpful intervention in reducing CB. Copyright © 2011 John Wiley & Sons, Ltd. Key Practitioner Message: Group cognitive–behavioural therapy is effective in the treatment of compulsive buying and superior to telephone‐guided self‐help. Preliminary data suggest that individuals who received telephone‐guided self‐help reported some improvement in compulsive buying compared with a waiting list condition. Further research is needed to investigate whether guided‐self help is effective in overcoming compulsive buying.